Consumo de drogas y su incidencia en el comportamiento de un hombre de 50 años del centro de rehabilitación de la ciudad de Ambato - Pilamunga Pilamunga, Galo Gualberto (2022)
The following investigative study was developed with the objective of establishing how drug use and its incidence influence the behavior of a 50-year-old man from the rehabilitation center of the city of Ambato, since a certain issue is considered a problem of a specific nature. Social that directly affects adults anyway, my purpose is to propose a proposal that allows me to carry out an adequate psychotherapeutic intervention and in this way be able to address the problem that affects the patient. The psychometric tools and techniques applied to obtain the necessary information will also be announced, in addition the results obtained in each of them are detailed, the symptomatological findings in each of its structures or functional areas are detailed, the corresponding diagnosis is established. Finally, a psychotherapeutic proposal is prepared in order to provide possible solutions.